Pengaruh Penggunaan Media Video Pembelajaran YouTube terhadap Hasil Belajar Matematika Siswa Sekolah Dasar (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The rapid development of educational technology has encouraged teachers to utilize various digital learning media, one of which is YouTube-based learning videos. This study aims to examine the effect of YouTube learning videos on elementary school students’ mathematics learning outcomes. The research employed a literature review method by analyzing and synthesizing findings from relevant journal articles, research reports, and other scholarly sources. Data were collected through document analysis and then categorized according to the impacts of YouTube learning media on mathematics learning. The findings indicate that the use of YouTube learning videos positively influences students’ mathematics achievement. The positive impacts include improvements in cognitive abilities, higher-order thinking skills, learning motivation, learning interest, mathematical reasoning, and conceptual understanding. In addition, YouTube learning videos provide flexible access to learning materials, allowing students to review explanations repeatedly according to their learning needs. Therefore, YouTube-based learning media can be considered an effective alternative to support mathematics learning in elementary schools.